0372 Patients' views and expectations on social work services in the occupational medicine clinic in the Maccabi Health service organisation. (23rd June 2014) - Moshe, Shlomo; Tzinamon, Tali; Chodick, Gabriel; Zack, Oren; Tal, Marla
Abstract : Objectives: To explore patients' expectations regarding the social work service and to deterrmine their satisfaction level with the care provided to them so far by the social worker in the framework of the occupational clinic. Method: This is a cross-sectional study which consists of Maccabi members of working age that visited occupational nedicine departments between September 2011 and July 2012 for the purpose of fitness-for-work evaluation who were referred to and met with a social worker. These members filled out an expectation and satisfaction questionnaire after meeting with the social worker. Results: A total of 203 questionnaire were filled out. Most of the patients were interested in receiving information about their benefits (85%). A smaller number of patients (39.2%) were interested in receiving help dealing with a family members' distress due to the loss of work ability of the patient. A very high percentage of the patients (97%) were satisfied with the social worker session. A correlation was found between the patients' expectations and their satisfaction with the amount of information they received (p > 0.01). Conclusions: This is a first study of this kind addressing social work services in a public occupational medicine services. The study shows the positive advantage of this service and a high patient satisfaction level with the social work service. The satisfaction level was high even though the patients' health status was relatively low. We recommend expanding the service beyond Maccabi onto other health service organisations.